Ras gene in marine mussels: A molecular level response to petrochemical exposure - Lima, I.
Mussels are susceptible to numerous toxicants and are often employed as bioindicators. This study investigated the status of the ras proto-oncogene in Mytilus galloprovincialis following petrochemical exposure. A M. galloprovincialis homologue of the vertebrate ras gene was isolated, showing conserved sequence in regions of functional importance and a high incidence of polymorphic variation. Mutational damage was investigated in mussels chronically exposed to the water-accommodated fraction of #4 fuel-oil (WAF), and in mussels collected along the NW coast of Portugal in sites with different levels of petrochemical contamination. A ras gene point mutation was identified in the codon 35 of one individual exposed to 12.5% WAF No mutations were detected in mussels from the WAF control or environmental samples. This represents the first report of a ras gene mutation, experimentally-induced by petrochemical exposure, in an invertebrate species. (c) 2008 Elsevier Ltd. All rights reserved.